INSECURITY IN NIGERIA, CAUSES, CONSEQUENCE AND SOLUTIONS - ADEBAYO SULAIMAN ADEODU; EBELOKU IYANDA ADEMOLA; BLESSING CLARA BABAFEMI (International Studies Journal)
Nigeria is facing high rates of crime; banditry has become a harsh reality in today’s Nigeria society. Hence, efforts of government have not yielded enough positive result. It is on this note that this study examines insecurity in Nigeria: causes, consequences and solutions. Data were collected using structured questionnaires to analyzed descriptive statistics such as Mean, standard deviation and rankings were used to determine the relationship between variables. Findings revealed that poverty, unemployment and illiteracy are the major causes of insecurity in Nigeria especially in the north east and south east of Nigeria. This was revealed with mean score of 4.26, 4.24 and 4.31 and standard deviation of 0.83, 0.82 and 0.87 respectively. In conclusion, eradication of poverty, provision of better job, free education at all levels will reduce insecurity to barest minimum.  The study recommended that government should empower the youth with vocational training, free education, non interest loans should be given to artisans and allow the youth in politics.